Antibiotic fosmidomycin protects bacteria from cell wall perturbations by antagonizing oxidative damage-mediated cell lysis - Yoshikazu Kawai; Jeff Errington (Frontiers in Microbiology)
Cell wall peptidoglycan is a defining component of bacterial cells, and its biosynthesis is a major target for medically important antibiotics. Recent studies have revealed that antibiotics can kill cells not only by their direct effects on wall synthesis, but also by downstream perturbations of metabolic homeostasis, leading to oxidative damage-mediated lysis. In this paper, we have investigated the killing effects of various effectors of cell wall inhibition, including an antibiotic inhibitor of isoprenoid synthesis, fosmidomycin, in Bacillus subtilis. We show that oxidative damage largely contributes to the toxic effect (rapid cell lysis) induced by inhibition of peptidoglycan synthesis, but not by inhibition of the isoprenoid synthetic pathway. Remarkably, intermediate concentrations of fosmidomycin, confer resistance to lysis when peptidoglycan synthesis is perturbed. We show that this is because fosmidomycin not only blocks peptidoglycan synthesis, but also impairs the synthesis of menaquinone, which, protects cells from respiratory chain-associated oxidative damage and lysis. Our results provide new insights into the critical involvement of metabolic pathways, such as isoprenoid biosynthesis, on the antibiotic efficacy and evasion by bacteria. This work advances our understanding of bacterial physiology as well as antibiotic activity and resistance.